SYAIR SURAT KAPAL ADAT PERKAWINAN MASYARAKAT KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU: PENDEKATAN EKSPRESIF - Dini Maulani; Syafrial Syafrial; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is titled Surat Kapal Poams of the Traditional Marriage from the Rengat sub-district of Indragiri Hulu Regency: an Expressive Approach. The background of this research is that surat kapal poams which only exists in Indragiri Hulu becomes extinct even though surat kapal poams are unique poams that only exist in Indargiri Hulu, Riau. The purpose of this study is to describe the author and authorship of surat kapal poams and describe the exspression of the author of surat kapal poams. This research is a descriptive qualitative research that describes the results of the research that has been done. Research conducted to obtain results discussing (1) the authors and authorship of surat kapal poams covering: 1) family background, 2) educational background, 3) profession, 4) social relations, 5) character, 6) creative process, 7) fellow profession, and 8) regeneration. Then (2) the expression of the author of surat kapal poams.Key Words: Surat Kapal Poams, Author, Authorship, Exspression of Author.